Unpacking the Institutional Complexity in Adoption of CSR Practices in Multinational Enterprises - Marano, Valentina; Kostova, Tatiana (Journal of Management Studies, 2016)
ABSTRACTMultinational enterprises (MNEs) operate in complex transnational organizational fields with multiple, diverse, and possibly conflicting institutional forces. This paper examines how such complex environments affect a firm's adoption of Corporate Social Responsibility (CSR) practices. To capture the effect of transnational fields, we consider the institutional influences of all country environments to which the firm is linked through its portfolio of operations and propose that these effects will be weighted depending on their relative salience. We identify a set of factors that make certain pressures more salient than others, including firm's economic dependence on a particular country, heterogeneity of institutional forces within the firm's transnational field, exposure to leading countries with more stringent CSR templates, and intensity and commitment to particular economic linkages (i.e., foreign direct investment versus international trade). Our hypotheses are tested and supported in a study of 710 US MNEs from 2007 to 2011 with global ties to over 100 countries.